Exercise-Induced Cognitive Improvement Is Associated with Sodium Channel-Mediated Excitability in APP/PS1 Mice. (18th March 2020) - Tan, Ya-Xin; Liu, Guang-Cai; Chen, Hong-Lan; Lu, Min-Nan; Chen, Bo; Hu, Tao; Zhang, Li; Mao, Rui; Li, Shan; Mei, Rong; Wang, Xu-Yang; Xiyang, Yan-Bin
Abstract : Elevated brain activation, or hyperexcitability, induces cognitive impairment and confers an increased risk of Alzheimer's disease (AD). Blocking the overexcitation of the neural network may be a promising new strategy to prevent, halt, and even reverse this condition. Physical exercise has been shown to be an effective cognitive enhancer that reduces the risk of AD in elderly individuals, but the underlying mechanisms are far from being fully understood. We explored whether long-term treadmill exercise attenuates amyloid precursor protein (APP)/presenilin-1 (PS1) mutation-induced aberrant network activity and thus improves cognition by altering the numbers and/or distribution of voltage-gated sodium channels (Nav) in transgenic mice. APP/PS1 mice aged 2, 3.5, 5, 6.5, 8, and 9 months underwent treadmill exercise with different durations or at different stages of AD. The alterations in memory, electroencephalogram (EEG) recordings, and expression levels and distributions of Nav functional members (Nav1.1 α, Nav1.2, Nav1.6, and Nav β 2) were evaluated. The results revealed that treadmill exercise with 12- and 24-week durations 1) induced significant improvement in novel object recognition (NOR) memory and Morris water maze (MWM) spatial memory; 2) partially reduced abnormal spike activity; and 3) redressed the disturbed cellular distribution of Nav1.1 α, aberrant Nav β 2 cleavage augmentation, and Nav1.6 upregulation. Additionally, APP/PS1 mice in the 24-week exercise group showed better performance in the NOR task and a large decrease in Nav1.6 expression, which was close to the wild-type level. This study suggests that exercise improves cognition and neural activity by altering the numbers and distribution of hippocampal Nav in APP/PS1 mice. Long-term treadmill exercise, for about 24 weeks, starting in the preclinical stage, is a promising therapeutic strategy for preventing AD and halting its progress.